Pengaruh Pembuatan Proposal Rencana Bisnis (Business Plan) Terhadap Kemampuan Berwirausaha di SMK Bhakti Husada - Hugo Aries Suprapto (Jurnal Ilmiah Wahana Pendidikan, 2019)
Influence of business plan proposal (business plan) is the beginning of human activity in developing its business. The creation of business plan proposals important things must be learned and understood. The training plan of business plan in SMK Bhakti Husada gives correlation (R) value of 0.411 and explained the percentage of influence of independent variable to the dependent variable called coefficient of determination which is the result of squaring R. From the coefficient of determination R2 contributed of 16.9%, while the rest is influenced by other variables. The value of t arithmetic = 2.387 with a significance value of 0.000 <0.05 then H0 is accepted, which means there is a significant effect (significant) variable making business plan proposals to entrepreneurship variables.